Effect of Different Levels of the Processed Lablab purpureus Seeds on Laying Performance, Egg Quality and Serum Parameters - Ragab , H.I.; Ati, K.A. Abdel; Kijora, C.; Ibrahim, S. (International Journal of Poultry Science, 2012)
L. purpureus is considered to substitute some of conventional plant protein sources in poultry diets. In 12 weeks feeding trial the processed L. purpureus seeds were investigated for its impacts on laying performance, egg quality and serum constituents of Hisex White hens. Diets contain 0, 5, 10, 15 and 20% L. purpureus were allotted randomly following completely randomized design to 25 units of three birds each. Hen day egg production, egg weight, egg mass, FCR and weight gains were significantly (p<0.01) high up to 10% L. purpureus. Shell percentage and thickness were significantly (p<0.05) high in control and 20% L. purpureus groups. 15 and 20% L. purpureus dietary groups were of high egg albumin index and percentage. The utmost (p<0.05) yolk index and percentage were shown in 15 and 10% L. purpureus groups, respectively. Comparable high Haugh units were shown in different treatment groups. 15% L. purpureus groups, recorded significant (p<0.01) high serum total protein and globulin. All L. purpureus treatment groups were of significant (p<0.05) low serum albumin. Serum glucose was significantly (p<0.01) lowered in L. purpureus groups, while serum cholesterol was insignificantly (p>0.05) reduced due to L. purpureus inclusion. The 20 and 10% L. purpureus groups when compared to control were found of low serum P and Ca, respectively. In conclusion, up to 10% dietary inclusion of L. purpureus is appropriate to provide similar laying performance as the standard layers diet.